The association with Down’s syndrome can affect phenotypic expression of Hashimoto’s thyroiditis in childhood - Zirilli, Giuseppina; Salzano, Giuseppina; Corica, Domenico; Ventrici, Claudia; Candela, Gilberto; Porcaro, Federica (Acta Biomedica Atenei Parmensis, 2016)
Background: It is not well known whether the association with Down’s syndrome (DS) may be able to affect the phenotypic expression of Hashimoto’s thyroiditis (HT). Objectives: To review the most recent literature data about the specific peculiarities of HT in DS children. Design: The main epidemiological features of DS-related HT were compared with those generally reported in HT children without DS. The prevalence rates of the different thyroid function patterns detected at the time of HT diagnosis and five years later were summarized in Tables 1 and 2. Conclusions: 1) the association with DS can condition a peculiar phenotypic expression of HT in pediatric age, as confirmed by the analysis of both epidemiological and biochemical features; 2) in DS children thyroid function status may be severely impaired both at HT presentation and some years later.